2009
DOI: 10.5558/tfc85091-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial harvesting on vertebrate species associated with late-successional forests in Ontario’s boreal region

Abstract: In the boreal forest region, partial-harvest silviculture has been garnering increasing interest as a means of maintaining wildlife species and habitat structure associated with late-successional forests. If late-successional species can find suitable habitat in partially harvested stands with a given level of structural retention, then partial harvesting might represent a viable silvicultural tool for maintaining wildlife dependent on mature or old-forest habitat within managed stands over time. Here we summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 76 publications
(60 reference statements)
3
34
0
Order By: Relevance
“…In contrast, early-seral-stage species, such as White-throated Sparrow (Zonotrichia albicollis Gmelin), Tennessee Warbler (Vermivora peregrina A. Wilson), Dark-eyed Junco (Junco hyemalis L.), and American Robin (Turdus migratorius L.) were more abundant in CPRS and CPPTM (LeBlanc 2009. The effects of CPRS and CPPTM are consistent with previous observations that low retention levels (<30%) would negatively affect mature forest species (Harrison et al 2005, Vanderwel et al 2009). Harrison et al (2005) suggested that 50% retention should be sufficient for maintaining most mature forest species.…”
Section: Partial Cutting Old-growth Stands and Animal Communitiessupporting
confidence: 80%
See 3 more Smart Citations
“…In contrast, early-seral-stage species, such as White-throated Sparrow (Zonotrichia albicollis Gmelin), Tennessee Warbler (Vermivora peregrina A. Wilson), Dark-eyed Junco (Junco hyemalis L.), and American Robin (Turdus migratorius L.) were more abundant in CPRS and CPPTM (LeBlanc 2009. The effects of CPRS and CPPTM are consistent with previous observations that low retention levels (<30%) would negatively affect mature forest species (Harrison et al 2005, Vanderwel et al 2009). Harrison et al (2005) suggested that 50% retention should be sufficient for maintaining most mature forest species.…”
Section: Partial Cutting Old-growth Stands and Animal Communitiessupporting
confidence: 80%
“…Harrison et al (2005) suggested that 50% retention should be sufficient for maintaining most mature forest species. Vanderwel et al (2009) suggested that some mature forest species, such as Brown Creeper, would still be affected by this retention level but that local extirpation would be unlikely. In our case, a 55% retention level appeared to be effective in maintaining old-growth species, including the Brown Creeper.…”
Section: Partial Cutting Old-growth Stands and Animal Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Retention of coarse woody material is an important part of sustaining forest productivity and biodiversity (Spies 1998, Shields et al 2007, Vanderwel et al 2009, OMNR 2010, though quantities vary considerably (Fig.. 4). Published volumes for CWD in northern hardwood and mixed forests of eastern North America show values ranging from 10.8 m 3 ha -1 to 136.7 m 3 ha -1 , and averaging 60.5 m 3 ha -1 (Fig.…”
Section: Discussionmentioning
confidence: 99%